1, 3‐Dipolar Cycloaddition of 4‐Chlorobenzonitrile Oxide with Some Dipolarophiles: Theoretical Analysis of Regioselectivity. (7th March 2013) - Bakavoli, Mehdi; Moeinpour, Farid; Sardashti‐Birjandi, Arezoo; Davoodnia, Abolghasem
<x xml:space="preserve">Abstract</x> Reaction of 4‐chlorobenzonitrile oxide (1) which was generated in situ with acrylo nitrile (3), vinyl acetate (1) and allyl bromide (1) as dipolarphile afforded the new cycloadducts 1, 1, and 1 compounds, respectively. Reactivity and regiochemistry of these reactions were investigated using activation energy calculations and density functional theory‐based reactivity indexes. The theoretical 13C NMR chemical shifts of the cycloadducts which were obtained by gauge‐invariant atomic orbital method were comparable with the observed values.